THE INFLUENCE OF SERVICE AND DESIGN CO-CREATION ON SALES VOLUME ENHANCEMENT: A CASE STUDY OF ALSA LEMON MSME IN SUKABUMI CITY - M Izzat Farsan Rahbani; Neneng Kartika Rini; Ika Sofia Rizqiani (Gunung Djati Conference Series, 2026)
This research aims to analyze the influence of co-creation through the dimensions ofdesign (Value Co-design) and service (Value Co-service) on increasing sales volume at UMKMAlsa Lemon in Sukabumi City. The research method employed is quantitative, utilizing linearregression analysis with primary data obtained through customer questionnaires. The resultsindicate that, simultaneously, collaborative product development variables contributesignificantly, accounting for 53.4% of the variation in sales volume. Partially, Value Co-designis proven to have a positive and significant influence (p < 0.05), making it the dominant factorin attracting purchasing interest through consumer involvement in designing physical productattributes. Meanwhile, Value Co-service acts as a supporting factor in maintaining customerloyalty through service interaction. This study also identifies an external factor of 46.6%, whichincludes pricing policies and distribution reach as operational supporting infrastructure. Theresearch concludes that the synergy between participatory product innovation andconventional marketing management is a key strategy in boosting the sales performance ofagribusiness MSMEs sustainably in the local market.